Two new species of Simulium (Gomphostilbia) (Diptera: Simuliidae) from Peninsular India with keys to Peninsular Indian members of the genus Simulium - Anbalagan, Sankarappan; Prasanna, Vimalanathan Arun; Dinakaran, Sundaram; Krishnan, Muthukalingan (Zootaxa, 2014)
Two new species of black flies, Simulium (Gomphostilbia) peteri sp. nov. and S. (G.) takaokai sp. nov., are described on the basis of reared adult, pupal and larval specimens collected from Peninsular India. These two new species are placed in the batoense species group within the subgenus Gomphostilbia. S. (G.) peteri sp. nov. is distinguished in the female by having a medium-sized round opening of the sensory vesicle and a large basal tooth on the claw, in the male by 12 vertical columns in the upper eye large facets, in the pupa by a ventral pair of 2 gill filaments somewhat thicker than the other filaments and in the larva by 5 hypostomal bristles per side lying parallel to the lateral margin. S. (G.) takaokai sp. nov. is characterized in the pupa by having the eight gill filaments with a medium-long common basal stalk and in the larva by the labral fan with 38 main rays and 4 hypostomal bristles on each side. Keys to 13 black fly species reported from Peninsular India are provided for females, males and pupae.